Private relations eaudiobook - Chamberlain, Diane (Tantor Media, 2016)
Welcome to the Chapel House, the old oceanfront mansion where a group of close friends share their hopes and dreams, and where love is sometimes an unexpected guest. Heartfelt and deeply moving, Private Relations won the 1989 RITA Award for Best Single Title Contemporary Novel from the Romance Writers of America.